Implementation of Al-Qur'an Hadith Learning in Class Ix MTs N 3 Karawang - Diva Harfi Mutmainah; Elia Nuryatin; Najwa Aulia; mohammad hafizh; Debibik Nabilatul Fauziah (CV. Kayaswara, 2025)
This study discusses the implementation of Al-Qur’an Hadith learning in the ninth grade at MTsN 3 Karawang, focusing on student engagement in the learning process. Interview results show that student participation in Al-Qur’an Hadith lessons tends to fluctuate and is greatly influenced by their mood and personal motivation. One of the main challenges is students’ difficulty in reading the Al-Qur’an or Arabic letters, which makes them less enthusiastic about following the lessons. To address this, the teacher provides exercises in writing Arabic letters and memorization tests, as well as strives to boost students’ enthusiasm through support, motivation, and humor in the classroom. These findings emphasize the importance of a flexible approach and emotional support from teachers to encourage students to be more active and interested in learning Al-Qur’an Hadith